The Role of Trust in Mediating the Influence of Perceived Value and Service Quality on Tenant Loyalty in Industrial Estates - Bayu Pamuji, Tri; Novandari, Weni; Pradisti, Larisa (DINASTI RESEARCH, 2025)
This study aims to examine the effect of perceived value and service quality on tenant loyalty in an industrial estate, with trust as a mediating variable. The research was conducted using a quantitative approach, involving 100 tenant respondents from a selected industrial area in Central Java, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that perceived value and service quality have a significant direct effect on tenant loyalty. In addition, both variables significantly influence trust, which in turn positively affects tenant loyalty. Trust also plays a significant mediating role in the relationship between perceived value and service quality with tenant loyalty. These findings highlight the importance of building trust as a psychological bridge that transforms perceived value and service quality into sustainable tenant loyalty. This study contributes to the literature on business-to-business (B2B) relationship management and provides practical insights for industrial estate managers to strengthen tenant retention through trust-based strategies.